Improving Thematic Learning Outcomes Of Class Vi Students Through Power Of Two Learning At Sd Negeri 013 Kunto Darussalam - Lili Suriani (Indonesian Journal of Basic Education, 2022)
This study aims to determine the use of The Power Of Two models in thematic learning can improve student learning outcomes in class VI SD Negeri 013 Kunto Darussalam. This research is a class action research (CAR) which is descriptive qualitative using a qualitative approach which is strengthened by a quantitative approach, taking the background of Negeri 013 Kunto Darussalam, while the object of research is to improve learning outcomes in thematic learning using The Power Of Two models. This research was conducted in two cycles and through four stages which included: (1) Planning, (2) Implementation, (3) Observation and (4) Reflection. Data obtained through observation, interviews, test work on questions and documentation. Data analysis was carried out using the results of cycle I and cycle II learning tests, the approach to cycle I showed that all learning activities had not been carried out well enough by students even though they had increased in cycle I compared to pre-cycle and were still at a low predicate, because the average percentage was still below 75%. Cycle II has shown satisfactory results both from student learning activities that have been in the predicate of sufficient, good and very good, while student learning outcomes have achieved an average of 86% with a classical percentage of 90% meaning that corrective action for the learning process is sufficient and meet the criteria